Short-chain fatty acids in schizophrenia: are they affected by a depressive state? - M. Couce-Sánchez; G. Paniagua; L. González-Blanco; A. García-Fernández; C. Martínez-Cao; C. Sabater; A. Margolles; J. Bobes; M. P. García-Portilla; P. Sáiz (European Psychiatry, 2024)
Introduction Short-chain fatty acids (SCFA) are bacterial metabolites that, within microbiome-gut-brain axis, make a promising research line on etiopathology of mental diseases like schizophrenia (SZ) and major depression disorder. Besides, depressive symptoms are frequent clinical features of SZ.